Comparative Antimicrobial Analysis of Chitosan Nanoparticles With Gentamicin And Chloramphenicol (Fountain Journal of Natural and Applied Sciences, 2019)
Chitosan has attained increasing commercial interest as suitable resource materials due to their excellent properties including biocompatibility, biodegradability, adsorption and ability to form films and to chelate metal ions. Antibiotics resistance has become rampant and nanoparticles are increasingly used to target microorganisms as an alternative to antibiotics. The research was conducted to produce and synthesize nanoparticles using the extract of chitosan and test the antimicrobial activity against some selected bacteria. Chitosan was produced by demineralization, deproteinization and deacetylation of oyster shell. The silver nanoparticle was synthesized from Chitosan and screened for in vitro antimicrobial activity against selected bacteria using agar well diffusion method. Synthesized nanoparticles were characterized using UV-VIS spectrophotometry, FTIR spectroscopy and Scanning Electron Microscopy. Chitosan nanoparticles showed some inhibiting properties against the growth of most of the organisms tested (Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Salmonella typhi). Most of the isolates were inhibited by both extracts. The positive control which was chloramphenicol and gentamycin inhibited the growth of all organisms except Salmonella typhi.Keywords: Chitosan, Silver nanoparticles, Agar well-diffusion, SEM, FTIR